2018
DOI: 10.1089/cap.2017.0140
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Trend in the Use and Long-Term Use of Benzodiazepines Among Young Adults

Abstract: Overall prevalence of BZD use among young adults decreased from 24.0 to 18.8 users per 1000 inhabitants in 2006-2014. Prevalence of long-term use decreased from 5.5 to 3.3 users per 1000 inhabitants. Overall BZD use was higher among females, whereas long-term use was more common among males. Use of anxiolytics was more common than use of hypnotics. Oxazepam, alprazolam, zopiclone, and zolpidem were the most used BZDs, whereas alprazolam and clonazepam were the substances with most long-term use. The use and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Individual European country studies on the use of anxiolytics confirm a north–south divide, with southern European countries reporting an increase in the use of anxiolytics from 2006 onwards, 35 whereas northern European countries have reported a decrease, particularly in younger age groups (18–25 years). 36 , 37 Our study found high rates of consumption of tranquilisers in Serbia (94·50 DDD per 1000 inhabitants per day) and Croatia (80·26 DDD per 1000 inhabitants per day), which was similar to rates reported in a 2018 study on the impact of socioeconomic instability on benzodiazepine exposure in three Balkan countries. 38 Although socioeconomic instability could explain the difference seen between three eastern European countries in that study, 38 our results suggest that, on a global level, socioeconomic unrest can only partly explain the variation in the consumption of tranquilisers.…”
Section: Discussionsupporting
confidence: 88%
“…Individual European country studies on the use of anxiolytics confirm a north–south divide, with southern European countries reporting an increase in the use of anxiolytics from 2006 onwards, 35 whereas northern European countries have reported a decrease, particularly in younger age groups (18–25 years). 36 , 37 Our study found high rates of consumption of tranquilisers in Serbia (94·50 DDD per 1000 inhabitants per day) and Croatia (80·26 DDD per 1000 inhabitants per day), which was similar to rates reported in a 2018 study on the impact of socioeconomic instability on benzodiazepine exposure in three Balkan countries. 38 Although socioeconomic instability could explain the difference seen between three eastern European countries in that study, 38 our results suggest that, on a global level, socioeconomic unrest can only partly explain the variation in the consumption of tranquilisers.…”
Section: Discussionsupporting
confidence: 88%
“…Similar trends have been found for z-hypnotics across other Nordic countries, including Denmark and Sweden, although the trends observed in Sweden have been somewhat inconsistent [ 42 , 54 ]. In Finland, declining trends have been observed for both benzodiazepines and z-hypnotics [ 50 ]. This indicates that the increased awareness of these drugs’ potential for misuse may have affected prescription practices.…”
Section: Discussionmentioning
confidence: 99%
“…There were also differences among the few international studies reporting recent trends of long‐term use of BZD, with a slight increase reported in Canada (2004–2013) 11 and a decrease observed in Finland (2006–2014), 13,21 while benzodiazepines alone have been decreased in Korea (2009–2013) 22 . In studies where benzodiazepines and z‐drugs were analyzed separately, a Canadian linked data study (2004–2013) reported a slight decline in long‐term benzodiazepine and an increase in long‐term z‐drug use, 11 whereas a US study using National Health and Nutrition Examination Survey data (1999–2014) reported an increase in long‐term use of both, benzodiazepines and z‐drugs 14 …”
Section: Introductionmentioning
confidence: 99%